The importance of mothers-in-law's employment for their daughter-in-law's labour market outcomes in West Germany: Results and mechanisms - Sophia Schmitz; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Social norms have been put forward as prominent explanations for the changing labour supply decisions of women. This paper studies the intergenerational formation of these norms, examining how they affect subsequent female labour supply decisions, taking into account not only the early socialization of women but also that of their partner. Using large representative panel data sets from West Germany, results suggest that women with partners who grew up with a working mother are more likely to participate in the labour force, work longer hours, and earn higher labour income. Our study can assess a variety of potential mechanisms for this intergenerational link. It cannot be explained by other confounding patterns. We find no evidence that this finding reflects assortative mating; rather, analysis suggests that the partner's preferences play a decisive role for the labour supply decision of partnered women. Our results suggest that policy measures supporting the labour force participation of today's mothers will increase the female labour force participation of the next generation.
Keywords: J22; Z13; J16; 330; social norms; labour supply; gender; Germany